Insight into the Significance of Viscous Dissipation and Heat Generation/Absorption in Magneto-Hydrodynamic Radiative Casson Fluid Flow With First-Order Chemical Reaction - Hassan, Ali; Hussain, Azad; Arshad, Mubashar; Gouadria, Soumaya; Awrejcewicz, Jan; Galal, Ahmed M.; Alharbi, Fahad M.; Eswaramoorthi, S. (Frontiers in Physics, 2022)
This study is an attempt to explore two dimensional magneto-hydrodynamic Casson fluid flow with heat generation or absorption, chemical reaction, and viscous dissipation under the effect of thermal radiation. Prescribed surface temperature (PST) and prescribed heat flux (PHF) cases have been taken into account to investigate the problem. The constitutive relations for Casson fluid incorporated with suitable boundary layer approximation theory have been utilized to achieve the flow model equations. The obtained highly non-linear partial differential equations cannot be solved analytically, so we transform them into first-order differential equations, then tackle them with the boundary value problem (BVP-4c) technique in Matlab. Radiation increment decreases primary and secondary velocity profiles abruptly in both cases. Heat generation and absorption augmentation decrease the thermal and momentum boundaries for both studied cases. The skin coefficient for PHF cases has decreased 80% when compared with PST cases. The increment in Casson parameter has enhanced the Nusselt number by 75% for the PST case, whereas the decline in Nusselt number has doubled for the PHF case with the increment in magnetic field. It is concluded that with the increment in Casson fluid, magnetic, radiation, and permeability parameter the Nusselt number has significantly increased for PST case. However, for these parameters, an abrupt declination in Nusselt number has been observed for PHF case. Results reported in this study for shear stress and Sherwood number are in complete agreement with already published previous work.